ZEUS next-to-leading-order QCD analysis of data on deep inelastic scattering - Chekanov, S; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; Bellagamba, L; Boscherini, D; et al. (2003)
Next-to-leading-order QCD analyses of the ZEUS data on deep inelastic scattering together with fixed-target data have been performed, from which the gluon and quark densities of the proton and the value of the strong coupling constant αs(Mz) were extracted. The study includes a full treatment of the experimental systematic uncertainties including point-to-point correlations. The resulting uncertainties in the parton density functions are presented. A combined fit for αs(MZ) and the gluon and quark densities yields a value for αs(M Z) in agreement with the world average. The parton density functions derived from ZEUS data alone indicate the importance of HERA data in determining the sea quark and gluon distributions at low x. The limits of applicability of the theoretical formalism have been explored by comparing the fit predictions to ZEUS data at very low Q2. © 2003 The American Physical Society.